The Effect of Facilities and Infrastructure Management and Teacher Performance on Student Learning Achievement - Suyanti, Susi; Manumanoso, M. Anggung; Rizki, Munawar (Jurnal Inovatif Manajemen Pendidikan Islam, 2026)
Student academic achievement is a key indicator of educational quality and is influenced by both instructional and organizational factors, including facility management and teacher performance. This study aims to examine the direct and indirect effects of school facilities and infrastructure management and teacher performance on students’ academic achievement. A quantitative approach with an explanatory survey design was employed. Data were collected from 226 students at MTsN 4 Aceh Utara using structured questionnaires and academic record documentation. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that facilities and infrastructure management has a positive and significant effect on students’ academic achievement and teacher performance. Teacher performance also shows a positive and significant effect on students’ academic achievement and serves as a mediating variable in the relationship between facilities management and academic achievement. These findings demonstrate that effective management of educational facilities supports a conducive learning environment and enhances teacher performance, which in turn contributes to improved student outcomes. This study contributes to the literature on educational management by providing empirical evidence from the context of Islamic secondary education and highlighting the integrated role of facilities management and teacher performance in improving students’ academic achievement.